1999
DOI: 10.1111/j.1600-0749.1999.tb00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypophysial and Meningeal Melanocytes in the Zucker Rat

Abstract: Melanocytes have not been described in the pituitary of mammals or in the meninges of the rat. In this paper, we report the presence of the cluster of melanocytes in the intermediate lobe of the pituitary and around the median eminence of the hypothalamus forming an 'infundibulo-hypophysial circle', and also describe the characteristics of meningeal melanocytes in Zucker rats. In the leptomeninges, numerous melanocytes were found on the ventrolateral surface of cerebral hemisphere in the area of the middle cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…1a) was amplified from the expressed plasmid. Classical melanocytes are effectively found in the skin and eye and nonclassical melanocytes are present in the heart (Mjaatvedt et al, 2005) and brain, at various levels in the meninges, including the leptomeninges and in the pituitary gland (Goldgeier et al, 1984;Fetissov et al, 1999). No Cre-ERT2 expression was detected in the spleen, liver, or kidney of the Tyr::Cre-ERT2 transgenic mice or in any of the wildtype tissues analyzed.…”
Section: Resultsmentioning
confidence: 79%
“…1a) was amplified from the expressed plasmid. Classical melanocytes are effectively found in the skin and eye and nonclassical melanocytes are present in the heart (Mjaatvedt et al, 2005) and brain, at various levels in the meninges, including the leptomeninges and in the pituitary gland (Goldgeier et al, 1984;Fetissov et al, 1999). No Cre-ERT2 expression was detected in the spleen, liver, or kidney of the Tyr::Cre-ERT2 transgenic mice or in any of the wildtype tissues analyzed.…”
Section: Resultsmentioning
confidence: 79%
“…In humans, melanocytes originate from the neural crest during early embryonic development and are normally found in the leptomeninges at the base of the brain, in the brainstem and in the spinal cord [21]. Although this has not been confirmed in humans, melanocytes are physiologically present in the pituitary of Zucker rats [22]. Therefore primary sellar melanocytic lesions may arise from the melanocytes harbored in the leptomeningeal tissue lining of the sellar floor or from the diaphragma sellae.…”
Section: Discussionmentioning
confidence: 97%
“…A study by Fetissov et al . (1999) demonstrated that in Zucker rats melanocytes are aggregated about leptomeningeal and hypophysial vessels 11 …”
Section: Discussionmentioning
confidence: 97%
“…Melanocytes are known to occur normally within the leptomeninges and are more concentrated at the base of the brain, particularly the ventrolateral surface of the medulla 10,11 . Primary sellar melanomas are believed to be leptomeningeal in origin, as are other intracranial melanomas 12 .…”
Section: Discussionmentioning
confidence: 99%